Effectiveness of Pranayama on the reduction of stress among 1st year nursing students due to adjustment problems in a nursing college - Bhattrai, Pooja; Banjade, Prakash; Rajak, Ashik (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Stress is a common feature in all our lives. It is often seen as a negative emotion but it plays an important role in survival, helping face threats, often motivating individuals and enhancing performance. Stress is a state of physical and psychological strain which imposes demands for adjustments upon the individual. It has been reported that student nurses are affected with stressors in academics, clinicals, and finances, due to parental expectations, competition for grades, and career choices. The aim of this study was to find the prevalence of stress among B.Sc. Nursing 1st year students due to adjustment problems and the effectiveness of pranayama in stress management.Method: A pre-experimental; one-group pretest-posttest design was conducted among fifty 1st year B.Sc. Nursing students in Karnataka College of Nursing in Bangalore between 25th August 2022 to 10th September 2022 using a questionnaire and rating scale to determine level of stress.Result: The comparison of pretest and post-test level of stress among 1st year B.Sc. nursing students revealed an overall reduction in mean % by 11.73 % with SD of 3.7. The obtained value was higher than the table value 4.804 which was highly significant at 0.05 level, indicating the practice of pranayama has a great influence in the reduction of stress.Conclusion: The findings of the study clearly showed that the practice of pranayama was effective in reduction of stress; enabling and empowering students with stress reduction methods, which in turn contributed to improving the quality of one’s health.